2022
DOI: 10.31073/abg.63.01
|View full text |Cite
|
Sign up to set email alerts
|

Historical Components of Scientific Potential Formation of the Institute of Animal Breeding and Genetics Named After M.V.ZUBETS of Naas

Abstract: The purpose of the article is to highlight the main organizational stages of establishment and creative searches of the zootechnical department of the Kiev Regional Agricultural Experimental Station, as well as the research units created on its basis as the forerunners of the formation of the scientific potential of the Institute of Animal Breeding and Genetics named after M.V.Zubets of NAAS. Research methods – general scientific (analysis, synthesis, classification), special historical (problem-chronological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…No less relevant and debatable at the present time is the question of the potential of internal tribal resources in solving this problem. The practice has shown that it is advisable to create a breeding base in meat cattle breeding using the world's best gene pool by purchasing Table 5, Continued outstanding animals, especially bulls and their sperm products ( Hladii et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…No less relevant and debatable at the present time is the question of the potential of internal tribal resources in solving this problem. The practice has shown that it is advisable to create a breeding base in meat cattle breeding using the world's best gene pool by purchasing Table 5, Continued outstanding animals, especially bulls and their sperm products ( Hladii et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…No less relevant and debatable at the present time is the question of the potential of internal tribal resources in solving this problem. The practice has shown that it is advisable to create a breeding base in meat cattle breeding using the world's best gene pool by purchasing Table 5, Continued outstanding animals, especially bulls and their sperm products ( Hladii et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the results of first-calf cows of the Ukrainian Black-and-White dairy breed assessment by udder measurements testified to its good development in most of the traits, both in shape and in manufacturability. And according to such important traits that characterize the udder size -length and width, they correspond to the target parameters of the desired lin-ear type measurements (42 and 33 cm) for first-calf cows of the Ukrainian Black-and-White dairy breed (Hladii et al, 2018).…”
Section: Table 1 Characteristics Of the First-calf Cows Of Dairy Catt...mentioning
confidence: 99%